Frequency of Hyperthyroidism in Hypokalemic Periodic Paralysis - Mukhtiar Ali Lakho, Abdul Ghafoor Magsi, Shabana Lakho, Muhammad Munwar Ali, Farukh Imtiaz Bhanbhro, Shoaib Ahmed Magsi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of hyperthyroidism in hypokalemic periodic paralysis Study Type: Cross-sectional study Place and Duration of Study: Department of Neurology, Chandka Medical College Hospital, Larkana from 1st January 2016 to 30th June 2016. Methodology: Eighty four patients with hypokalemic periodic paralysis of both sexes aged 18 to 60 years enrolled. Later on, the blood sample was collected and sends to LINAR Hospital for measurement of serum TSH, FT3 and FT4. The hormone assays was analyzed by chemiluminescence assay using ADVIA Centuar manufactured by SIEMENS NewYork. Results: The mean age was 40.24±9.96 years, 49 (58.3%) were males and 35 (41.7%) were females, 57 (67.9%) has duration of illness was >7 days and 27 (32.1%) had duration of illness >7 days. Mean TSH was 0.48±0.25, mean FT3 was 198.17±19.38 and mean FT4 was 19.43±6.65. The frequency of hyperthyroidism in hypokalemic periodic paralysis was 29 (34.5%) cases. Conclusions: The frequency of hyperthyroidism in hypokalemic periodic paralysis was 34.5%.